Considerations for Treatment in Clinical Care of Spinal Muscular Atrophy Patients - Stephanie Voight; Kapil Arya (Children, 2024)
Spinal Muscular Atrophy is a neurodegenerative disease which can lead to muscle weakness, paralysis, and in some cases death. There are many factors that contribute to the severity of symptoms and those factors can be used to determine the best course of treatment for the patients. We looked through published literature to create a set of considerations for treatment in patients with Spinal Muscular Atrophy including age, type, SMN2 copies, and any familial considerations. This can serve as a guide for what to consider in the treatment of SMA patients clinically.